Personal Peacefulness and Cyber-Bystanding of Internet Users in Indonesia - Nurfitriany Fakhri; Faradillah Firdaus; Irdianti; Sahril Buchori; Ria Andriany Fakhri (Jurnal Pendidikan Agama Islam, 2024)
Purpose – As internet use grows, cyberbullying has become more common, especially in schools. People who witness cyberbullying (cyber-bystanders) strongly influence these incidents, but little is known about their behavior. To reduce cyberbullying, we need to understand what affects cyber-bystanding. This study examines whether personal peacefulness can predict how people act as cyber-bystanders. Design/methods/approach – This quantitative correlational study examined 127 Indonesian internet users (36 males, 91 females). Data were collected using the Self Perception Scale and Cyberbullying Bystander Scale, with regression analysis employed to analyze the relationship between variables. Findings – Results revealed a significant relationship between personal peacefulness and defender bystander behavior. However, no significant relationships were found with passive or reinforcer bystander behaviors. Gender analysis showed that males exhibited higher levels of personal peacefulness than females. Additionally, males were more likely to act as reinforcer bystanders, supporting cyberbullying behavior, compared to females. Research implications/limitations – This study reveals how personal peacefulness relates to cyber-bystanding among Indonesian internet users. The findings help understand social behavior in schools where cyberbullying often occurs. These insights can help develop strategies to prevent harmful cyber-bystanding behavior by focusing on personal peacefulness. Originality/value – While cyberbullying behavior in Indonesia has been extensively studied, research on cyber-bystanding remains limited, primarily documented through news articles. This study represents the first investigation of the relationship between personal peacefulness and cyber-bystanding in Indonesia. Future research should explore these variables in relation to other factors and different demographic groups to expand the current understanding of cyber-bystanding behavior in the Indonesian context.